Metabolic mediators of the impact of general and central adiposity measures on cardiovascular disease and mortality risks in older adults: Tehran Lipid and Glucose Study. Issue 11 (28th March 2017) - Kazempour‐Ardebili, Sara; Ramezankhani, Azra; Eslami, Ali; Akbarpour, Samaneh; Azizi, Fereidoun; Hadaegh, Farzad
Abstract: Aims: To investigate the relationship between body mass index, waist circumference, waist‐to‐hip ratio and waist‐to‐height ratio, as well as the mediating factors through which they might exert their risk for cardiovascular disease/coronary heart disease and mortality events in the older Iranian population during a median follow up of 9.5 years. Methods: The study population included participants, aged ≥65 years, free of cardiovascular disease at baseline. The confounder‐adjusted hazard ratio was calculated for a 1‐SD change in each anthropometric measure with and without adjustment for hypercholesterolemia, diabetes and hypertension. Results: During the study follow up, 193 participants developed their first cardiovascular disease event and 183 deaths occurred. No association was found between cardiovascular disease/coronary heart disease and body mass index, even in the confounder‐adjusted models. Central adiposity measures showed a significant risk for cardiovascular disease events in the confounder‐adjusted model ranging from hazard ratio 1.16 (95% confidence interval 1.02–1.33) for waist‐to‐hip ratio to 1.21 (95% confidence interval 1.03–1.42) for waist‐to‐height ratio. Adjustment for hypertension alone or in combination with other metabolic mediators attenuated the hazard ratio to null. Although hypercholesterolemia did not show any mediating effect of central adiposity measures for cardiovascular disease/coronary heart disease, hypertension was the most powerful mediator, accounting for 30–45% of the excess risk. Conclusions: Central rather than general adiposity showed a significant role in determining cardiovascular disease/coronary heart disease risk. The harmful effect of central adiposity was completely attributable to mediators, especially hypertension. Clinical interventions for control of mediators focusing on hypertension should be emphasized.Geriatr Gerontol Int 2017; 17: 2017–2024 .